Cerebrospinal fluid flow increases from newborn to adult stages. Issue 9 (2nd August 2018) - Di Palma, Camille; Goulay, Romain; Chagnot, Sebastien; Martinez De Lizarrondo, Sara; Anfray, Antoine; Salaun, Jean‐Philippe; Maubert, Eric; Lechapt‐Zalcman, Emmanuèle; Andreiuolo, Felipe; Gakuba, Clément; Emery, Evelyne; Vivien, Denis; et al.
ABSTRACT: Solute transport through the brain is of major importance for the clearance of toxic molecules and metabolites, and it plays key roles in the pathophysiology of the central nervous system. This solute transport notably depends on the cerebrospinal fluid (CSF) flow, which circulates in the subarachnoid spaces, the ventricles and the perivascular spaces. We hypothesized that the CSF flow may be different in the perinatal period compared to the adult period. Using in vivo magnetic resonance imaging (MRI) and near‐infrared fluorescence imaging (NIRF), we assessed the dynamic of the CSF flow in rodents at different ages. By injecting a contrast agent into the CSF, we first used MRI to demonstrate that CSF flow gradually increases with age, with the adult pattern observed at P90. This observation was confirmed by NIRF, which revealed an increased CSF flow in P90 rats when compared with P4 rats not only at the surface of the brain but also deep in the brain structures. Lastly, we evaluated the exit routes of the CSF from the brain. We demonstrated that indocyanine green injected directly into the striatum spread throughout the parenchyma in adult rats, whereas it stayed at the injection point in P4 rats. Moreover, the ability of CSF to exit through the nasal mucosa was increased in the adult rodents. Our results provide evidence that the perinatal brain has nonoptimal CSF flow and exit and, thus, may have impaired clean‐up capacity. © 2018 Wiley Periodicals, Inc. Develop Neurobiol, 2018